KARAKTERISTIK SMOOTHIE CAMPURAN BUAH JAMBU BIJI MERAH (Psidium guajava L.) DAN JERUK MANIS (Citrus sinensis) DENGAN PENAMBAHAN WHEY PROTEIN CONCENTRATE 80 (WPC 80) - Ainiyah, Nidaul; Suter, I Ketut; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 6 No 2 (2017): Jurnal ITEPA, 2017)
This research was conducted to determine the effect of additional WPC 80 to the red guava and sweet orange blend on characteristics smoothie. The completely randomized block design was used in the research with the treatment of WPC 80 additional in different concentration level (0%, 0,5%, 1%, 1,5% and 2%). The treatment repeated 3 times for producing 15 experimental units. Data were analyzed with variance analysis followed by Duncan multiple range test, if they were significant different effect (P<0,05). The result of this research showed that the additional of 2% WPC 80 produce the best smoothie characteristics (water content 89,13 %, protein content 6,35 %, total soluble solids 11,40 °brix, pH 4,54, vitamin C 64,05 mg/100 ml, viscositas 288 m.Pas, dietary fiber 1,37%), with color rather like, flavour like, taste creamy and like, texture thick and rather like.